STUDI KELAYAKAN PEMANFAATAN PRODUK BERBABAHAN BAKU PALA : (BASIC PRODUCT) - Pelupessy, James (Politeknik Negeri Ambon, 2022)
The aims of this study were 1) to find out the process of refining nutmeg oil in the sole owner of the plantation (parkenir) from the Dutch heritage of Van Den Broeke and the surrounding nutmeg farmers to meet the raw materials for producing nutmeg oil. 2) Analyze the feasibility of refining nutmeg oil. 3) Analyze sensitivity. Market aspect analysis was carried out by searching digital markets such as shopee, Bukalapak to find out nutmeg oil products with various packages and nutmeg oil content abys aromatherapy and selling prices for various package sizes. The number of buyers for various sizes shows the consumer's response to nutmeg oil as aromatherapy. Analysis of technical aspects is obtained by collecting data on technology, processing, and investment in distillation equipment at the Van den Broeke parkenir in Walang village, Banda sub-district. These data form the basis of production capacity analysis. Investment planning, the need for raw materials and labor increased gradually over three years. The number of workers in the micro industry is not more than five people. This research was conducted at Parkenir Van den Broek, Walang Village, Banda sub-district, Central Maluku Regency. The determination of the research location was carried out purposively, with the consideration that Parkenir Van den Broek is the only nutmeg plantation with an area of ​​12.5 ha and has distillation equipment in Banda. The results of the calculation of the investment feasibility criteria in this production process are: 1. The NPV (Net Present Value) of the nutmeg oil refining industry generates an NPV or net profit at the end of the project, which is Rp. 53,836,063 Because the NPV value is > 0, this business is feasible. 2. Net B/C (Net Benefit Cost Ratio) The nutmeg oil refining industry produces a Net B/C value of 1.26. This means that the nutmeg oil refining industry is feasible because the Net B/C value is > 1. 3. The IRR (Internal Rate Of Return) The nutmeg oil refining industry is feasible because it obtains an IRR > 18%, namely 54%.